2013
DOI: 10.1128/jb.02107-12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Rieske-Type Alkane Monooxygenase System in Pusillimonas sp. Strain T7-7

Abstract: The cold-tolerant bacterium Pusillimonas sp. strain T7-7 is able to utilize diesel oils (C 5 to C 30 alkanes) as a sole carbon and energy source. In the present study, bioinformatics, proteomics, and real-time reverse transcriptase PCR approaches were used to identify the alkane hydroxylation system present in this bacterium. This system is composed of a Rieske-type monooxygenase, a ferredoxin, and an NADH-dependent reductase. The function of the monooxygenase, which consists of one large (46.711 kDa) and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…In another study, the purified large subunit of a novel alkane monooxygenase (belonging to Class B ROs), identified from a cold-tolerant Pusillimonas sp. T7-7, showed NADH-dependent alkane monooxygenase activity (Li et al 2013). Transformation of aromatic hydrocarbons has also been attained by heterologous expression of the terminal oxygenase components using non-specific ET proteins complemented by the host strain (Mukerjee-Dhar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the purified large subunit of a novel alkane monooxygenase (belonging to Class B ROs), identified from a cold-tolerant Pusillimonas sp. T7-7, showed NADH-dependent alkane monooxygenase activity (Li et al 2013). Transformation of aromatic hydrocarbons has also been attained by heterologous expression of the terminal oxygenase components using non-specific ET proteins complemented by the host strain (Mukerjee-Dhar et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, few bacterial RO homologs with novel functions, such as oxidative cyclization during biosynthesis of certain antibiotics, hydroxylation and desaturation of short-chain tertiary alcohols and alkane monooxygenation, have been reported in recent years (Sydor et al 2011; Schäfer et al 2012; Li et al 2013). This suggests that ROs bear much more catalytic potential than previously realized.…”
Section: Introductionmentioning
confidence: 99%
“…A. beijerinckii ZRS was isolated from an oil‐contaminated soil sample from the Xinjiang oil field in China and the culture conditions for this strain were based on Huang et al . T7‐7 was isolated from the seabed mud of the Bohai Sea in a petroleum‐contaminated region . Diesel oil was purchased from a local service station of Sinopec Group and the light crude oil was donated by Shengli Oil Field of China.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, integral membrane non-heme iron (AlkB) or cytochrome P450 enzymes (CYP153) oxidize pentane (C 5 ) to hexadecane (C 16 ), and alkanes longer than heptadecane are metabolized by a novel alkane dioxygenase, putative flavin-binding monooxygenase (AlmA), or long-chain alkane monooxygenase (LadA) ( Maeng et al, 1996 ; Feng et al, 2007 ; Throne-Holst et al, 2007 ). However, a recent study showed that a novel Rieske-type alkane monooxygenase degrades pentane (C 5 ) to tetracosane (C 24 ) using NADH as a cofactor ( Li et al, 2013 ). In addition, many bacteria possess multiple alkane hydroxylases (AH), and therefore, it is possible that a wide range of alkanes can be degraded by one microorganism ( Whyte et al, 1998 ; Rozhkova-Novosad et al, 2007 ; Amouric et al, 2010 ; Liu et al, 2011 ; Park et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%